Greenequality : determination of socio-spatial urban landscape typology - Golubić, Stjepko (Array, 2018)
This paper explores the history of limitations in use and accessibility of city landscapes. Case study analysis covers six examples of parks and residential square gardens. Mutual comparison offers a new socio-spatial urban landscape typology, which precedes the selection of models of rehabilitation for city landscapes. The results show that designed landscapes are used not only to mitigate, but also to intensify socio-spatial inequality.